Assessment of bone-fill following regenerative periodontal therapy by image subtraction using commercially available software - Yellarthi, PavanKumar; Rampalli, ViswaChandra; Anumala, Naveen; Devaraju, RamaRaju (Journal of Indian Academy of Oral Medicine and Radiology, 2014)
Context: There are few applicable methods and scant literature on using non-specific image analysis software to assess and quantify post-periodontal surgery bone-fill. Aims: The present study describes the method of digital subtraction radiography (DSR) and morphometric area analysis (MA) in assessing bone-fill following regenerative periodontal therapy by using two image processing tools. Settings and Design: For the bone-fill assessment, radiographs of 78 angular bone defects from 30 subjects who underwent periodontal flap surgery with hydroxyapatite bone graft placement were utilized. Materials and Methods: The initial radiographic image obtained at baseline was subtracted from the radiographic images taken at 12/24 weeks by using the commercially available image processing software. After digital subtraction, the digitized and excluded interdental bone was transferred to open source software for area calculation. Bone-fill calculated by using DSR and MA was compared to the bone-fill values obtained by using the 1 mm 2 counting grid placed over the digital sensor. Statistical Analysis: Intragroup comparison of bone-fill between various groups was performed using repeated measures analysis of variance (ANOVA) followed by multiple comparisons using Bonferroni correction. One-way ANOVA followed by the post hoc test was used for intragroup and intergroup comparison. Results: DSR and MA showed higher mean bone-fill levels over radiographic grid. Conclusion: Considering that the software aims to reduce the inaccuracy behind manual assessment of bone-fill, the overestimation of bone-fill as compared to a grid may be attributed to the enhanced sensitivity of the method.